South East Asian migrant experiences in regional Victoria: Exploring well-being. (December 2014) - Townsend, Rob; Pascal, Jan; Delves, Mel
This article outlines a recent pilot project in Bendigo that collected baseline data in order to develop a preliminary understanding of regional migration experiences. The literature indicated that migrant experiences in Australian regional communities are under-researched. Sixty participants from South East Asia, who have migrated to Bendigo, Victoria within the last five years, completed a mixed-methods survey. The key findings reported upon are socio-structural factors, social connectedness and psychosocial well-being. Crucial factors such as culture, spirituality and non-English-language, link to the more complex issues of personal, social and cultural identity. These findings are significant in adding to the limited data and discussion about newly arrived migrants in rural and regional communities. There are sociological implications from this preliminary data concerning social capital and psychosocial well-being. There are also implications for policy development and professional practice for migration to rural and regional communities.